The estimation of maximum ground acceleration value in West Sumatra region based on the M 8.8 SR earthquake scenario using MC Guire (1963) and Donovan (1973) empirical formula. - Mia Leviana; Syafriani Syafriani; Ardiyansyah Sabarani (Department of Physics – Universitas Negeri Padang UNP, 2017)
West Sumatra is one of the regions is prone to earthquakes because it the positions of an active seductions zone between the Indo-Australian plate and the Eurasian Plate is along the Sumatra fault. The maximum ground acceleration is one of the important parameters, because it describes the strength of earthquake vibration ever happened. Therefore, it is necessary to do measurement and calculation of ground acceleration caused by earthquakes. By knowing the maximum ground acceleration values in an area, we can know which area is prone to earthquakes. Data were analyzed by an earthquake scenario is created, and the epicenter 1.00o LS 99.00o BT, M = 8.8 magnitude and a depth of 30 km. Formulation of Mcguire (1963) and Donovan (1973) is used to find the value of the maximum ground acceleration and Murphy O'Brein empirical formula to find the value of intensity. The maximum ground acceleration value for each county / city in West Sumatra is calculated by using the position of the district / city as a reference point. The results of data processing maps obtained Peak Ground Acceleration (PGA) and the intensity of the earthquake. The analysis showed that the value of the PGA and the greatest intensity being Pariaman with a value PGA 177.59 gal and has a value of 7.67 MMI intensity. Then the value of the maximum ground acceleration both owned by the Mentawai Islands with 176.72 gal and intensity value is 7.66 MMI.